Impact of gut probiotic metabolites on phenylketonuria - Kalla Veedu, Anjana; Vijayakumar, Sujithra; Joseph, Hannah A.; Thomas, John (Frontiers in Cellular and Infection Microbiology, 2025)
Phenylketonuria is an unusual inherited metabolic disease induced by mutations of the phenylalanine hydroxylase gene, resulting in phenylalanine accumulation. The current treatments only focus on restricting lifelong dietary intake of phenylalanine, posing a significant challenge to concordance and living standards. Emerging evidence on phenylketonuria disorders underscores the gut microbiome involving probiotics as a key mediator of host metabolic processes. This review encompasses the insights into the pathophysiology of phenylketonuria, gut probiotics, the amino acid metabolism of phenylalanine, the mechanism of action of probiotics, and the therapeutic potential of the treatments available.